Let's solve your equation step-by-step.
3
(
3
x
−
4
)
=
−
2
(
1
−
4
x
)
Step 1: Simplify both sides of the equation.
3
(
3
x
−
4
)
=
−
2
(
1
−
4
x
)
(
3
)
(
3
x
)
+
(
3
)
(
−
4
)
=
(
−
2
)
(
1
)
+
(
−
2
)
(
−
4
x
)
(Distribute)
9
x
+
−
12
=
−
2
+
8
x
9
x
−
12
=
8
x
−
2
Step 2: Subtract 8x from both sides.
9
x
−
12
−
8
x
=
8
x
−
2
−
8
x
x
−
12
=
−
2
Step 3: Add 12 to both sides.
x
−
12
+
12
=
−
2
+
12
x
=
10
Answer:
Step-by-step explanation:
Answer:
you can't answer it without knowing how much money they have to multiply it by the 8% to find out what you'll be paying out to California each month
Step-by-step explanation:
you have to know your monthly income to know how much you're paying out in California